Training to be a spinal endoscopic surgeon: What matters? - Xie, Yizhou; Zhou, Qun; Wang, Yongtao; Feng, Chengzhi; Fan, Xiaohong; Yu, Yang (Frontiers in Surgery, 2023)
Objectives Spine endoscopic surgery has been promoted rapidly in the past decade attracting more and more spine surgeons of young generations to be dedicated in. However, it has long been denounced of its long learning curve as a factor to impede the state-of-the-art technique to continually develop. Current study is aimed to dig out what vitally matters in the educational process for being a spine endoscopic surgeon. Methods The online survey consisted of fourteen compulsory questions and was distributed in April and May 2022 through the First Chinese Spinal Endoscopic Surgeons Skills Competition. Reminders were sent to improve the response rate. Results We received 637 responses out of 893 emails which had been sent out. 375 surgeons (76.7%) most frequently used endoscopic technique in their practices. Regardless of their different background, 284 of them (75.7%) thought it would be necessary for a young spine endoscopic surgeon to perform 300 cases independently in order to become proficient, followed by 500 cases (43, 11.5%), 100 cases (40, 10.7%) and 1000 cases (8, 2.1%). According to the surgeons, the most difficult aspect to master endoscopic technique is disparate surgical view (255, 68%), followed by novel instrument adaption (86, 22.9%) and hand-eye coordination (34, 9.1%). The most helpful training method to facilitate spine endoscopic surgeon of younger generation to improve is operating on simulation models or cadaver courses(216, 57.6%), followed by online or offline theoretical courses (67, 17.9%), acquiring the opportunities during surgeries (51, 13.6%) and frequently participating in surgeries as an assistant (41, 10.9%). Conclusion From the perspective of surgeons, to be skilled in spine endoscopic surgery has to overcome a steep learning curve. However, training system should be attached more importance to make it more accessible for surgeons of younger generations to operate on simulation models or take cadaver courses.